Enhanced Production Of Poly (3-Hydroxybutyrate-Co-4-Hydroxybutyrate) With High 4hb Unit Composition Using Transformant Cupriavidus sp.USMAA1020 - Hambali, Norhafini (2017)
Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] copolymer is one of emerging biopolymer which possess suitable properties to be applied in medical applications. P(3HB-co-4HB) with high 4HB unit is favorable as this enhance the biocompatibility and mechanical properties of this copolymer as implantable and absorbable biomaterial. However, biosynthesis of P(3HB-co-4HB) in single-stage cultivation produces low 4HB unit composition with low productivity. Cupriavidus sp. USMAA1020, a bacterium isolated from Malaysian environment, was capable to synthesize P(3HB-co-4HB) with different 4HB unit compositions but only to a maximum of 70 mol% through single-stage cultivation.